PENEGAKAN HUKUM PIDANA PROFESIONAL BERPIHAK PADA FAKTA HUKUM DAN KEADILAN (Universitas Suryakancana, 2017)
Law enforcement criminal court must dare to be assertive in the process of law enforcement should not be legalitik the chained stream normatik dogmatik, it's time to find the ideal concept in accordance with the sense of Justice in favour of society ( public) and realized that the dynamic laws of development. The small settlement of cases does not always have to be boiled down to the Court, using the means and utilizing the penal imprisonment or confinement sentence need to be considered again for the sake of the values of Justice. Investigator required material provisions of law and guided by formyl applicable investigation is part of the process of criminal law enforcement needed material, so that truth refers to legal facts and evidence obtained in order to obtain legal certainty that comes down to fairness. Keywords: Police, Law Enforcement, Professional, Justice.